2003
DOI: 10.1002/macp.200350075
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Poly(methyl methacrylate)/Poly(vinylidene fluoride) Blends in the Presence of High‐Pressure Carbon Dioxide

Abstract: Previous efforts have demonstrated that high‐pressure CO2 can markedly influence the phase behavior of amorphous polymer blends. In this work, we examine the effect of high‐pressure CO2 on the miscibility of blends composed of glassy poly(methyl methacrylate) (PMMA) and semicrystalline poly(vinylidene fluoride) (PVDF). Blends of this type are known to exhibit lower critical solution temperature (LCST) behavior with partial miscibility up to ≈50–60 wt.‐% PVDF at ambient conditions. Two miscible PMMA/PVDF blends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 80 publications
(87 reference statements)
0
20
0
Order By: Relevance
“…These endotherms indicate T m values (133°C) lower than that of neat PVDF (160°C) because of the imperfect formation of PVDF crystals under restricted chain motion at high-viscosity conditions and temperatures near the blend T g . The CO 2 -induced crystallization of PVDF in PVDF/PMMA blends has been established by Chiou et al, [118] but crystallization at low PVDF concentrations has been reported by Walker et al [107] The difference between the two studies can be attributed to the difference in CO 2 pressure ranges examined: 1-2.5 MPa versus 17-31 MPa, respectively. Higher CO 2 pressures apparently promote greater plasticization and thus enable higher chain mobility, which facilitates the formation of PVDF crystals even in blends predominantly composed of PMMA.…”
Section: Scco 2 -Induced Crystallization/meltingmentioning
confidence: 88%
See 4 more Smart Citations
“…These endotherms indicate T m values (133°C) lower than that of neat PVDF (160°C) because of the imperfect formation of PVDF crystals under restricted chain motion at high-viscosity conditions and temperatures near the blend T g . The CO 2 -induced crystallization of PVDF in PVDF/PMMA blends has been established by Chiou et al, [118] but crystallization at low PVDF concentrations has been reported by Walker et al [107] The difference between the two studies can be attributed to the difference in CO 2 pressure ranges examined: 1-2.5 MPa versus 17-31 MPa, respectively. Higher CO 2 pressures apparently promote greater plasticization and thus enable higher chain mobility, which facilitates the formation of PVDF crystals even in blends predominantly composed of PMMA.…”
Section: Scco 2 -Induced Crystallization/meltingmentioning
confidence: 88%
“…Crystallization has also been induced by CO 2 in polymer blends consisting of at least one crystallizable component. For instance, PVDF in a PVDF/PMMA blend has been reported [63,107,118] to crystallize upon exposure to CO 2 . However, the molecular process of crystallization in such blends is more complex than in neat semicrystalline PVDF since the presence of PMMA effectively serves to deplasticize the PVDF and hinders crystallization in blends with more than ca.…”
Section: Scco 2 -Induced Crystallization/meltingmentioning
confidence: 98%
See 3 more Smart Citations